Burden of malignant neoplasm of bone and articular cartilage from 1990 to 2021 and its predictions to 2030 in China compared with world - Chen, Cheng; Zheng, Xu; Zhang, Yi; Li, ZhenDong; Li, Bing; Yang, YunFeng; Zhang, WeiBin (Frontiers in Oncology, 2025)
ObjectiveTo comprehensively examine the incidence and mortality of malignant neoplasms of bone and articular cartilage (MNBAC) in China compared with the world, as well as its age-specific patterns and sex disparities.MethodsThe MNBAC burden in China and the world was systematically assessed from 1990 to 2021 based on the Global Burden of Disease 2021, including incidence and mortality data. The estimated annual percentage change was calculated. The pattern of age and gender distribution was carried out. The future trends of MNBAC incidence and mortality through 2030 were predicted using the Bayesian age-period-cohort model.ResultsFrom 1990 to 2021, China experienced rising trends in both the incidence and mortality of MNBAC, increasing at a much faster pace than the world. Before 2005, crude incidence and mortality rates in China increased but plateaued thereafter. In contrast, age-standardized rates displayed a decreasing trend from 2005 onward. During this period, the world experienced relatively stable incidence and mortality rates. The incidence and mortality rates of MNBAC increase with age. The MNBAC burden is higher in males. The rise in incidence and mortality rate in China was predominantly in the elderly. The burden prediction for MNBAC to 2030 showed that China would experience a more significant drop in incidence and mortality rates for MNBAC, along with a decrease in the incidence and mortality cases.ConclusionsFrom 1990 to 2021, the MNBAC burden in China remains heavy, with incidence and mortality increasing much faster than in the world. The projection results indicate a promising outlook for the future, which is encouraging news. Men and the elderly should be the key target for the public health policies of MNBAC.